2023
DOI: 10.1200/jco.2023.41.16_suppl.10013
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol for prevention of heart failure in anthracycline-exposed survivors of childhood cancer: Results from COG ALTE1621.

Abstract: 10013 Background: Carvedilol improves cardiac function in patients with heart failure (HF), but remains untested as cardioprotective therapy in long-term childhood cancer survivors at risk for HF due to high-dose anthracycline exposure. We hypothesized that low-dose carvedilol would be safe and efficacious in reducing anthracycline-related heart failure risk in long-term survivors without evidence of HF. Methods: This was a randomized, double-blind, placebo-controlled phase 2B trial (NCT02717507) conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our results are timely, given the recently reported findings from the randomized, double-blind, placebo-controlled phase IIB trial (ClinicalTrials.gov identifier: NCT02717507), which suggested that among survivors exposed to doxorubicin-equivalent anthracycline doses ≥250 mg/m 2 with a baseline LVEF ≥55% and/or shortening fraction ≥28%, 2-year administration of low-dose carvedilol was significantly associated with better left ventricular end-diastolic diameter and end-systolic wall stress compared with placebo. 68 Notably, treatment effects varied by time since cancer diagnosis ( P = .008), suggesting a greater benefit to cardioprotective therapy with carvedilol in longer-term survivors. In a second trial, randomized atorvastatin administration in adults with lymphoma receiving anthracyclines was shown to be associated with a reduction in the incidence of an absolute decline in LVEF ≥10% from baseline to an LVEF <55% at 1 year (9% atorvastatin v 22% placebo; P = .002).…”
Section: Discussionmentioning
confidence: 96%
“…Our results are timely, given the recently reported findings from the randomized, double-blind, placebo-controlled phase IIB trial (ClinicalTrials.gov identifier: NCT02717507), which suggested that among survivors exposed to doxorubicin-equivalent anthracycline doses ≥250 mg/m 2 with a baseline LVEF ≥55% and/or shortening fraction ≥28%, 2-year administration of low-dose carvedilol was significantly associated with better left ventricular end-diastolic diameter and end-systolic wall stress compared with placebo. 68 Notably, treatment effects varied by time since cancer diagnosis ( P = .008), suggesting a greater benefit to cardioprotective therapy with carvedilol in longer-term survivors. In a second trial, randomized atorvastatin administration in adults with lymphoma receiving anthracyclines was shown to be associated with a reduction in the incidence of an absolute decline in LVEF ≥10% from baseline to an LVEF <55% at 1 year (9% atorvastatin v 22% placebo; P = .002).…”
Section: Discussionmentioning
confidence: 96%
“…Although the overall adherence to cardiovascular screening recommendations among this selected population is disconcerting, our findings provide hope that streamlined communication between oncologists, patients, and primary care could improve awareness, adherence, and overall cardiovascular outcomes. As strategies emerge to prevent or treat anthracycline-associated cardiomyopathy, either through the reduction of modifiable disease risk factors or cardiac remodeling as heart function begins to worsen, 6 , 32 , 33 multimodal strategies to address guideline-concordant survivorship care are needed. The CHIIP intervention trial in progress focuses on providing personalized SCPs to patients and PCPs.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, trials of screening strategies using advanced echocardiographic indices, such as global longitudinal strain (GLS) 17 have suggested possible benefit from flagging subclinical left ventricular systolic dysfunction and guiding the deployment of potentially disease-modifying therapies. [18][19][20][21][22][23][24][25] Therefore, there is an unmet need to design scalable yet personalized tools to enable the timely identification of patients who might benefit from more intensive follow-up. Furthermore, it is critical that these tools are accessible and affordable, ensuring equitable and broad access across high and low-resource settings.…”
Section: Introductionmentioning
confidence: 99%